Pre-Developmental Indices of Children in the Process of Acquisition of Virtues - Seyyede Fateme Musavi (اخلاق وحیانی, 2016)
Virtues are the positive, stable character traits that emerge in the course of time and in response to the shared experiences of children with their environment in developmental stages of life and by continuation and repetition they become habitus. In this way, they establish a basis for a virtuous society. The aim of this paper is to overview the thoughts of developmental theorists such as Piaget, Kochanska, Ibn Miskawayh, and Nasir al-Din al-Tusi and to present research evidence about the formation of virtues in children. According to the majority of developmental views, we can acknowledge that there are some prerequisites for virtuous behavior before the beginning of developmental stages, including pre-ethical sensitivity, shared intention, ethical ego, and conscience. These prerequisites can help the emergence and stabilization of virtues in children by enriching the environmental experiences in the developmental stages. So the supportive and warm relationship of parents and providing rich social experiences could make an appropriate ground for strength and stability of virtuous behavior in children.